Wastewater and Septic System Management for the COVID-19 Virus: Frequently Asked Questions - Mary G. Lusk (EDIS)
This new 3-page publication of the UF/IFAS Department of Soil and Water Sciences answers common questions about the potential role of wastewater and septic systems in transmission of COVID-19. It is intended as guidance for the general public. Written by Mary G. Lusk. https://edis.ifas.ufl.edu/ss692